The Nitrosopumilus maritimus CdvB, but Not FtsZ, Assembles into Polymers. (2nd June 2013) - Ng, Kian-Hong; Srinivas, Vinayaka; Srinivasan, Ramanujam; Balasubramanian, Mohan
Abstract : Euryarchaeota and Crenarchaeota are two major phyla of archaea which use distinct molecular apparatuses for cell division. Euryarchaea make use of the tubulin-related protein FtsZ, while Crenarchaea, which appear to lack functional FtsZ, employ the Cdv (cell division) components to divide. Ammonia oxidizing archaeon (AOA) Nitrosopumilus maritimus belongs to another archaeal phylum, the Thaumarchaeota, which has both FtsZ and Cdv genes in the genome. Here, we used a heterologous expression system to characterize FtsZ and Cdv proteins from N. maritimus by investigating the ability of these proteins to form polymers. We show that one of the Cdv proteins in N. maritimus, the CdvB (Nmar_0816), is capable of forming stable polymers when expressed in fission yeast. The N. maritimus CdvB is also capable of assembling into filaments in mammalian cells. However, N. maritimus FtsZ does not assemble into polymers in our system. The ability of CdvB, but not FtsZ, to polymerize is consistent with a recent finding showing that several Cdv proteins, but not FtsZ, localize to the mid-cell site in the dividing N. maritimus . Thus, we propose that it is Cdv proteins, rather than FtsZ, that function as the cell division apparatus in N. maritimus .